2014
DOI: 10.1111/peps.12091
|View full text |Cite
|
Sign up to set email alerts
|

What Will the Boss Think? The Impression Management Implications of Supportive Relationships With Star and Project Peers

Abstract: Although impression management scholars have identified a number of tactics for influencing supervisor evaluations, most of those tactics represent supervisor-targeted behaviors. This study examines the degree to which employees form supportive relationships with peers for impression management purposes. In so doing, we explore this intriguing question: Will employees gain more from forming supportive relationships with "stars" (i.e., top performers who are "on the fast track" in the organization) or "projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 92 publications
2
37
1
1
Order By: Relevance
“…The mean definitional correspondence level for the resulting three‐item procedural timeliness scale was 5.63. This value matches or exceeds other uses of this technique (Colquitt, Baer, Long, & Halvorsen‐Ganepola, ; Gardner, ; Hinkin & Tracey, ; Long, Baer, Colquitt, Outlaw, & Dhensa‐Kahlon, ; Rodell, ).…”
Section: Studysupporting
confidence: 81%
See 1 more Smart Citation
“…The mean definitional correspondence level for the resulting three‐item procedural timeliness scale was 5.63. This value matches or exceeds other uses of this technique (Colquitt, Baer, Long, & Halvorsen‐Ganepola, ; Gardner, ; Hinkin & Tracey, ; Long, Baer, Colquitt, Outlaw, & Dhensa‐Kahlon, ; Rodell, ).…”
Section: Studysupporting
confidence: 81%
“…Repeated‐measures analysis of variance (ANOVA) revealed that the items had statistically significantly stronger correspondences with the procedural timeliness definition than with the procedural justice definition ( t = 12.14, p < 0.001). Moreover, the correspondence with the timeliness definition was again at acceptable levels, relative to past results (Colquitt et al., ; Gardner, ; Hinkin & Tracey, ; Long et al., ; Rodell, ). Taken together, these results illustrate that the three timeliness items are more content‐valid indicators of procedural timeliness than procedural justice.…”
Section: Studysupporting
confidence: 56%
“…Students rated the correspondence between the items and the definition of situational aesthetics, resulting in a mean of 5.23 out of 7.00. This result also compares favorably to other uses of the procedure (Colquitt et al, 2014;Gardner, 2005;Hinkin & Tracey, 1999;Long et al, 2015;Rodell, 2013).…”
Section: Methodsmentioning
confidence: 52%
“…Participants were asked to rate the extent to which the items matched the definition of situational normality using a seven-point scale: 1 = Item is an extremely bad match to the definition to 7 = Item is an extremely good match to the definition. The mean level of definitional correspondence was 5.72 out of 7.00-a level that compares favorably to other uses of this procedure (Colquitt et al, 2014;Gardner, 2005;Hinkin & Tracey, 1999;Long, Baer, Colquitt, Outlaw, & Dhensa-Kahlon, 2015;Rodell, 2013). Newcomers were asked to consider the setting in which their work occurs, including the physical appearance of places and things.…”
Section: Methodsmentioning
confidence: 99%
“…This piece has (at the time of writing) been cited no less than 287 times, many of which report empirical studies. For the purpose of the current essay, I focus on the recent article by Long, Baer, Colquitt, Outlaw, and Dhensa‐Kahlon (), where the authors tested the idea that “employees form supportive relationships with peers for impression management purposes” (p. 463). Notably, Long and his colleagues state that their work “builds and tests theory about the impression management implications of employee relationships with peers” (p. 464).…”
Section: Why Do We Need Theory Articlesmentioning
confidence: 99%